Using Smartphones to Assist People with Down Syndrome in Their Labour Training and Integration: A Case Study - Gomez, Javier; Torrado, Juan Carlos; Montoro, Germán (Wireless Communications and Mobile Computing, 2017)
This article describes a proposal and case study based on mobile phones and QR Codes to assist individuals with cognitive disabilities in their labour training and integration. This proposal, named AssisT-Task, is a full functional mobile application for Android smartphones and offers step-by-step guidance, establishing a learning method through task sequencing. It has been tested with a group of 10 users and 2 types of labour tasks. Through 7 recorded sessions, we compared the performance and the learning progress with the tool against the traditional assisting method, based on paper instructions. The results show that people with cognitive disabilities learnt and performed better and faster when using AssisT-Task than the traditional method, particularly on tasks that require cognitive effort rather than manual skills. This learning has proved to be essential to obtain an adequate degree of personal autonomy for people with cognitive impairment.